Sifat Fisik Farmaseutik Tablet Hisap Herbal Yang Menggunakan PVP K-30 Dan Gom Arab Sebagai Pengikat - Haris, Zulfiah; Mirawati, Mirawati; Nurlina, Nurlina (PHARMACY UMI JOURNAL SYSTEM, 2024)
Tablets are pharmaceutical preparations that are most widely used by the public compared to other pharmaceutical preparations. One type of tablet is lozenges which are solid preparations containing one or more medicinal ingredients, generally with flavorful and sweet ingredients, which can make the tablet dissolve or disintegrate slowly in the mouth. Polyvinyl pyrylone K-30 (PVP K-30) binder has an advantage over other binders, as it can increase the hardness of tablets, making tablets a compact preparation. Arabic gum also has good flow properties, pharmacologically inert, has good compressibility and compactness. The purpose of the review is to determine the pharmaceutical properties of herbal lozenges that use PVP K-30 and Arabic gum as binders. The method used in reviewing this review is an electronic literature study by accessing journal search sites related to the keyword